2015
DOI: 10.15566/cjgh.v2i2.78
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the global context for cross-cultural healthcare work by regions of the world

Abstract: Healthcare missionaries (n=393) from 18 English-speaking countries, serving in 67 countries, were surveyed. With an average of 11 years of field experience and working primarily in the local language, participants in this study were able to report on healthcare situations and experience for expatriate healthcare missionaries in their countries of service. The healthcare institutions in most countries of the world were reported to be improving. Most countries were reported hospitable to the presence of expatria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Difficulty in obtaining licensure or work permits and inability to work in one's field have been recognized as significant problems before. 2,4,6 Nonetheless, several of our grant recipients reported that they arrived at their mission stations without adequate preparation for licensure or permits or without ensuring that they would be able to work in their fields. Some said they were advised that preparations were not critical and that they could manage the arrangements after arrival.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Difficulty in obtaining licensure or work permits and inability to work in one's field have been recognized as significant problems before. 2,4,6 Nonetheless, several of our grant recipients reported that they arrived at their mission stations without adequate preparation for licensure or permits or without ensuring that they would be able to work in their fields. Some said they were advised that preparations were not critical and that they could manage the arrangements after arrival.…”
Section: Discussionmentioning
confidence: 98%
“…According to previous reports of reasons for missionary attrition, correlation between the missionaries and their sending organizations tends to be low. 2,6 The information in our report was not obtained in a structured, prospective fashion but was instead gleaned from unstructured notes. However, the information in this report is consistent with our experience obtained in other venues.…”
Section: Recommendationsmentioning
confidence: 99%
“…The world is changing, 22 and the role of the healthcare missionary is also changing. 17 New focuses such as medical research, residency training and systematic management of chronic diseases also have opportunities for healthcare missions to support the development of strong national health care systems in developing settings.…”
Section: Aim 2: Developing Effective International Healthcare Educatorsmentioning
confidence: 99%